Decreasing deceased donor transplant rates among children (≤6 years) under the new kidney allocation system. Issue 7 (7th February 2018) - Shelton, Brittany A.; Sawinski, Deirdre; Ray, Christopher; Reed, Rhiannon D.; MacLennan, Paul A.; Blackburn, Justin; Young, Carlton J.; Gray, Stephen; Yanik, Megan; Massie, Allan; Segev, Dorry L.; Locke, Jayme E.
Abstract : The Kidney Allocation System (KAS) was implemented in December 2014 with unknown impact on the pediatric waitlist. To understand the effect of KAS on pediatric registrants, deceased donor kidney transplant (DDKT) rate was assessed using interrupted time series analysis and time‐to‐event analysis. Two allocation eras were defined with an intermediary washout period: Era 1 (01/01/2013‐09/01/2014), Era 2 (09/01/2014‐03/01/2015), and Era 3(03/01/2015‐03/01/2017). When using Cox proportional hazards, there was no significant association between allocation era and DDKT likelihood as compared to Era 1 (Era 3: aHR: 1.07, 95% CI: 0.97‐1.18, P = .17). However, this was not consistent across all subgroups. Specifically, while highly sensitized pediatric registrants were consistently less likely to be transplanted than their less sensitized counterparts, this disparity was attenuated in Era 3 (Era 1 aHR: 0.04, 95%CI: 0.01‐0.14, P < .001; Era 3 aHR: 0.33, 95% CI: 0.21‐0.53, P < .001) whereas the youngest registrants aged 0‐6 experienced a 21% decrease in DDKT likelihood in Era 3 as compared to Era 1 (aHR: 0.79, 95% CI: 0.64‐0.98, P = .03). Thus, while overall DDKT likelihood remained stable with the introduction of KAS, registrants ≤ 6 years of age were disadvantaged, warranting further study to ensure equitable access to transplantation. Abstract : Under the new kidney allocation system, pediatric registrants under age 6 experienced a significant decline in deceased donor kidney transplantation, suggesting the need for further monitoring of transplant rates among these registrants.